#Learning: The use of back channel technology in multi-campus nursing education. (September 2015) - Yates, Karen; Birks, Melanie; Woods, Cindy; Hitchins, Marnie
Summary: This paper reports on the results of a study into the use of microblogging technology (TodaysMeet) in large, multi-site lectures in a nursing program. The aim of this study was to investigate students' use of the technology and their perceptions of its value in stimulating engagement in a complex learning environment. The study demonstrated that students like the anonymity that the technology provided, allowing them to ask questions without fear of appearing less competent than their peers. Many of the respondents commented positively on the opportunity to engage with students and the lecturer at other campuses. While some students appreciated the opportunity to interact and have feedback from peers, others saw this as a negative aspect of the technology. This study suggests that, used appropriately, microblogging can be incorporated into large lectures to promote student participation and engagement and ultimately enhance the learning process. Highlights: Back channels can increase student engagement and participation in large lectures. Misuse of back channels must be managed effectively to maximise learning. The anonymity of back channel use can encourage students to ask questions.